IDENTIFICATION OF SETTLEMENT PRIOR TO THE ADDITION OF MSW LAYERS IN MSW SETTLEMENT MECHANISM IN LANDFILL - HADINATA ( NIM: 35312003 ), FEBRIAN
The lack of settlement studies has led to considerable uncertainty in the design and monitoring of landfills in Indonesia.Settlements are often overlooked in landfill design, so estimates of the lifetime of landfill become under-estimate. Mechanisms in MSW settlement in landfill include immediate compression and secondary compression, which is seen in MSW's compressibility behavior. The parameters used are the immediate compression ratio (Cc') which describes the compression behavior in the immediate compression phase, the secondary compression ratio (Cα) which describes the compression behavior in mechanical creep and biocompression phase.There are four types of landfill settlement estimation models including; soil mechanics based model, empirical model, rheological model and biodegradation related model.Thisresearch included measurement ofartificial wasteÃ‚Â’s compressibility with compression cell and, simulation of MSW settlement in landfill in three lysimeters. Furthermore, the development of estimation model of MSW settlement was done by incorporating pre-settlement factor pre-addition of MSW layer In order to measure MSW compressibility, a laboratory scale of compression cell tool was made with mould diameter and a high of 350- and 500-mm.The compression test was carried out with the initial pressure and the added pressure in accordance with the addition of pressure received by MSW due to the weight of the MSW layer above it.The test was performed on MSW samples of high density paper (PaperHD), MSW of medium-density paper (PaperMD), and MSW compost with moderate density (CompostMD). The paper represents fresh organic MSW with large pores, while compost represents MSW that has been degraded with smaller pore size and structure.Leachate is allowed to exit the compression cell tool.The test is performed by reference to ASTM D2435-96 test standard - Standard Test Method for One - Dimensional Consolidation Properties of Soils.From the test results in the compression cell, we get the value of Cc' for PaperHD, PaperMD and CompostMD, respectively - 0.0696; 0.2949 and 0.0932. While the value of Cα for PaperHD, PaperMD and CompostMD, respectively - 0.0056; 0,0211 and 0.0060. The test results showed the relationship between initial density and components to MSW compressibility. Three lysimeters of 820 mm diameter and height of 2000-, 3000- and 2000-mm respectively were prepared for simulatedMSW settlement in landfill. The sample used was MSW taken from one of the temporary waste stations in Bandung. Three MSW sample layers were inserted into the lysimeter, with the time lag of the sample input to the lysimeter interlayer being two days. MSW sample composition was dominated by food waste, paper, plastic and leaves.The sample contained high moisture content and organic matter, with moisture content of 69.05% (% of wet weight) and volatile content of 78.72% (% of dry weight). The density (bulk) of MSW in the lysimeter ranges from 0.41 to 0.64 tons/m3. Three variants of the sample in the three lysimeters were: organic MSW with a height of each layer of about 35 cm (MSWorganic), mixed MSW with each layer approximately 70 cm (MSWmixed-1) and mixed MSW with each layer approximately 35 cm (MSWmixed- 2). Rain water and leachate were allowed to enter and exit the lysimeter. The test was performed by reference to ASTM D2435-96 test standard.From the test results, obtained Cc'values for MSWorganic, MSW mixed-1 and MSW mixed-2 samples, each of 0.4177; 0.3917 and 0.3615.While the Cα values for the sample ofMSWorganic, MSW mixed-1 and MSW mixed-2, respectively 0.0602; 0.0887 and 0.0586.The compression ratio values (Cc'and Cα) of the MSW sample were high, due to the high water content and organic content of the sample.The organic composition affected the behavior of MSW which became more compressible. The height of layers were also directly proportional to MSW compressibility. From the results of the simulation in three lysimeters, it was known that the initial settlement of MSW was quite large before the addition of MSW layer was done, between 10 to 17%. The modification of the settlement estimation model was made by adding the settlement factor before adding the MSW layer. The detection results showed that the initial settlement was a linear regression model of settlement vs logarithm of time. The initial settlement equation is a combination of two proposed new parameters ie; the initial compression ratio (C0) is bound to the logarithmic time parameter, and the constant (a) reflects the strain at t = 1 day.Thus, the original settlement estimation model is a combination of settlement in the immediate compression phase and the secondary compression phase, being a combination of settlement in initial compression phase, the immediate compression phase and the secondary compression phase.This modification is able to decrease the difference between estimated and real settlement value in the lysimeter.